Achieving National Integration and Spiritual Harmony Through Rabindranath Tagore's Gitanjali - Sarmatha, S. (Jaffna Science Association, University of Jaffna, Sri Lanka, 2016)
By promoting National integration and Harmony through the literature it is possible to provide peaceful resolution for national and global problems and is able to build up a harmonious civilization of humankind. Rabindranarth Tagore, a Bengali poet, philosopher, artist, playwright, composer, novelist and India's first Nobel laureate, articulated the idea of creating global harmony through his works. He had deep sympathy for the poor and tried to uphold universal humanistic values. His poetry drew from traditional Vaisnava folk lyrics and is deeply mystical. The verses in Gitanjali are beautiful prayers for Lord. It is important to understand his works with social consciousness. His unfathomable pain and unshaken devotion to God are captured in Gitanjali. The main objective of this paper is to examine how Rabindranatha Tagore’s Gitanjali promotes the concepts of National integration and Spiritual Harmony. It tries to achieve peaceful nation through self-enlightenment and it binds the concepts of self and nation. The qualitative methodology has been carried out through texts, books, journals, essays and articles. This research consists of analytical method. This research will help to the younger generation to understand the national culture and ethics. Through this understanding it is possible to strengthen world peace and to build up a harmonious society.
Keywords: National integration; Spiritual Harmony; Social consciousness; Self and Nation